PEMANFAATAN TEMPURUNG KELAPA SEBAGAI BAHAN BAKU ARANG AKTIF DAN APLIKASINYA UNTUK PENJERNIHAN AIR LIMBAH INDUSTRI PETIS DI TAMBAK LOROK SEMARANG - . Suhartana (JURNAL ILMIAH MOMENTUM, 2007)
Waste Piece of Coconut shell used in society often only used upon which burn or firewood. Some furniture industries minimize there, exploited as a tool of physic educative and souvenir. In other hand, can be taken away from piece of coconut shell could to raw material of active charcoal. Chemical content of active charcoals is carbon compound, is very good for process of liquid material purification, inorganic and also organic material goodness. In this research is existing active charcoal, used to treatment waste water Petis factory at Tambak lorok  Semarang. Result after treatment by active charcoal pH, BOD, COD, TSS were decrease, but colour the waste water is clear.   Keyword: piece of coconut shell, active charcoal, waste water.